Lyophilized açaí pulp (Euterpe oleracea Mart) attenuates colitis-associated colon carcinogenesis while its main anthocyanin has the potential to affect the motility of colon cancer cells - Fragoso, Mariana F. [UNESP]; Romualdo, Guilherme R. [UNESP]; Vanderveer, Lisa A.; Franco-Barraza, Janusz; Cukierman, Edna; Clapper, Margie L.; Carvalho, Robson F. [UNESP]; Barbisan, Luis F. [UNESP] (Elsevier, 2018)
This study evaluated the possible protective effects of lyophilized açaí pulp (AP) in a colitis-associated carcinogenesis (CAC) rat model and the modifying effect of cyanidin 3-rutinoside (C3R) on the motility of RKO colon adenocarcinoma cells, using the wound healing assay. Male Wistar rats were induced to develop CAC using 1,2-dimethylhydrazine (DMH) and 2,4,6-trinitrobenzene acid (TNBS). Animals were randomly assigned to different groups that received basal diet or basal diet supplemented with 5.0% or 7.5% lyophilized AP. The findings indicate: 1) C3R (25 μM) has the potential to reduce RKO cell motility in vitro; 2) ingestion of lyophilized AP reduces the total number of aberrant crypt foci (ACF), ACF multiplicity, tumor cell proliferation and incidence of tumors with high grade dysplasia; 3) AP increases the gene expression of negative regulators of cell proliferation such as Dlc1 and Akt3, as well as inflammation (Ppara). Thus, lyophilized AP could exert a potential antitumor activity.
Keywords: Colitis; Colon carcinogenesis; Cyanidin 3-rutinoside; Lyophilized açaí pulp; Prevention